Highly Reduced Plastid Genomes of the Non-photosynthetic Dictyochophyceans Pteridomonas spp. (Ochrophyta, SAR) Are Retained for tRNA-Glu-Based Organellar Heme Biosynthesis - Kayama, Motoki; Maciszewski, Kacper; Yabuki, Akinori; Miyashita, Hideaki; Karnkowska, Anna; Kamikawa, Ryoma (Frontiers in Plant Science, 2020)
Organisms that have lost their photosynthetic capabilities are present in a variety of eukaryotic lineages, such as plants and disparate algal groups. Most of such non-photosynthetic eukaryotes still carry plastids, as these organelles retain essential biological functions. Most non-photosynthetic plastids possess genomes with varied protein-coding contents. Such remnant plastids are known to be present in the non-photosynthetic, bacteriovorous alga Pteridomonas danica (Dictyochophyceae, Ochrophyta), which, regardless of its obligatory heterotrophic lifestyle, has been reported to retain the typically plastid-encoded gene for ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) large subunit (rbcL). The presence of rbcL without photosynthetic activity suggests that investigating the function of plastids in Pteridomonas spp. would likely bring unique insights into understanding the reductive evolution of plastids, their genomes, and plastid functions retained after the loss of photosynthesis. In this study, we demonstrate that two newly established strains of the non-photosynthetic genus Pteridomonas possess highly reduced plastid genomes lacking rbcL gene, in contrast to the previous report. Interestingly, we discovered that all plastid-encoded proteins in Pteridomonas spp. are involved only in housekeeping processes (e.g., transcription, translation and protein degradation), indicating that all metabolite synthesis pathways in their plastids are supported fully by nuclear genome-encoded proteins. Moreover, through an in-depth survey of the available transcriptomic data of another strain of the genus, we detected no candidate sequences for nuclear-encoded, plastid-directed Fe–S cluster assembly pathway proteins, suggesting complete loss of this pathway in the organelle, despite its widespread conservation in non-photosynthetic plastids. Instead, the transcriptome contains plastid-targeted components of heme biosynthesis, glycolysis, and pentose phosphate pathways. The retention of the plastid genomes in Pteridomonas spp. is not explained by the Suf-mediated constraint against loss of plastid genomes, previously proposed for Alveolates, as they lack Suf genes. Bearing all these findings in mind, we propose the hypothesis that plastid DNA is retained in Pteridomonas spp. for the purpose of providing glutamyl-tRNA, encoded by trnE gene, as a substrate for the heme biosynthesis pathway.